2017
DOI: 10.1016/j.physleta.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Self-acceleration in non-Hermitian systems

Abstract: We study self-acceleration in PT and non-PT symmetric systems. We find some novel wave effects that appear uniquely in non-Hermitian systems. We show that integrable self-accelerating waves exist if the Hamiltonian is non-Hermitian. We find that self-accelerating constant intensity waves are possible even when gain and loss are not balanced in the system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Before discussing this point, we remind the reader about the self-accelerating waves, which is a non-integrable mathematical solution and hence physically impossible to be realized. However, it was shown that such solutions can still be used as nondiffracting waves up to a large distance if they were truncated [18,19]. In a similar fashion, we claim that our solution can also be used to construct non-diffracting beams.…”
Section: Continuous Family Of Stationary Solutions At the Exceptional...supporting
confidence: 60%
“…Before discussing this point, we remind the reader about the self-accelerating waves, which is a non-integrable mathematical solution and hence physically impossible to be realized. However, it was shown that such solutions can still be used as nondiffracting waves up to a large distance if they were truncated [18,19]. In a similar fashion, we claim that our solution can also be used to construct non-diffracting beams.…”
Section: Continuous Family Of Stationary Solutions At the Exceptional...supporting
confidence: 60%
“…Before discussing this point, we remember the selfaccelerating waves, which is a non-integrable mathematical solution and hence physically impossible to be realized. However, it was shown that such solutions can still be used as nondiffracting waves up to a large distance if they were truncated [28,29]. In a similar fashion, we state that the solutions for the semi-infinite lattice can be used to construct non-diffracting beams in the finite lattices.…”
Section: Continuous Family Of Stationary Solutionsmentioning
confidence: 65%
“…As a result, in Hermitian systems, self-acceleration happens exclusively for non-integrable waves. It was recently demonstrated that it happens even for integrable waves in non-Hermitian systems [2], and the new wave packets were produced using the inverted harmonic potential eigenstates in [3]. These novel wave packets contain boundless energy and a distinct self-focusing property.…”
mentioning
confidence: 99%